Social work practice on combating alcoholization of the indigenous population of Kamchatka: The concept of the "Northern gene" - Igorevna Kirillova , Alina (Universidad del Zulia, 2022)
The article is devoted to the problem of alcoholization of the indigenous population of Kamchatka, as well as concepts and theories explaining the problem of a sharp spike in alcohol dependence of the peoples of the North in the 1970s – 1980s. The concept (idea) of the so-called "northern gene" had been one of the logical explanations for a long time. However, today it is actively criticized. Even before the idea of the northern gene was formed, there had been an active struggle against the alcoholization of the population of Siberia and the Far East. These practices are no less important for understanding the current situation and finding solutions to this humanitarian problem. El artículo está dedicado al problema del alcoholismo de la población indígena de Kamchatka, así como a los conceptos y teorías que explican el problema del fuerte aumento de la dependencia del alcohol de los pueblos del Norte en los años 70-80. El concepto (idea) del llamado "gen del norte" ha sido una de las explicaciones lógicas durante mucho tiempo, sin embargo, hoy en día se critica activamente. Incluso antes de que se formara la idea del gen nórdico, había habido una lucha activa contra la alcoholización de la población de Siberia y el Lejano Oriente. Estas prácticas no son menos importantes para entender la situación actual y encontrar soluciones a este problema humanitario.